2007
DOI: 10.1128/mcb.00128-07
|View full text |Cite
|
Sign up to set email alerts
|

P-Body Formation Is a Consequence, Not the Cause, of RNA-Mediated Gene Silencing

Abstract: P bodies are cytoplasmic domains that contain proteins involved in diverse posttranscriptional processes, such as mRNA degradation, nonsense-mediated mRNA decay (NMD), translational repression, and RNAmediated gene silencing. The localization of these proteins and their targets in P bodies raises the question of whether their spatial concentration in discrete cytoplasmic domains is required for posttranscriptional gene regulation. We show that processes such as mRNA decay, NMD, and RNA-mediated gene silencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

50
683
4
10

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 619 publications
(765 citation statements)
references
References 64 publications
50
683
4
10
Order By: Relevance
“…Nonetheless, their data also implicated differences in the regulation of GWB formation in Drosophila from that in human. For example, Ago2-knockdown disassembled GWB and long double-stranded RNA did not restore GWB in LSm1-knockdown or rck/p54-knockdown cells in Drosophila (Eulalio et al, 2007b). These apparent discrepancies with our data may be attributed to the potential difference in the function of GWB components and in the RNAi pathway between Drosophila and human cells (Lee et al, 2004;Okamura et al, 2004).…”
Section: Regulation Of Gwb Assemblycontrasting
confidence: 95%
See 1 more Smart Citation
“…Nonetheless, their data also implicated differences in the regulation of GWB formation in Drosophila from that in human. For example, Ago2-knockdown disassembled GWB and long double-stranded RNA did not restore GWB in LSm1-knockdown or rck/p54-knockdown cells in Drosophila (Eulalio et al, 2007b). These apparent discrepancies with our data may be attributed to the potential difference in the function of GWB components and in the RNAi pathway between Drosophila and human cells (Lee et al, 2004;Okamura et al, 2004).…”
Section: Regulation Of Gwb Assemblycontrasting
confidence: 95%
“…We speculate that under certain circumstances, GWB may serve as markers for siRNA/miRNA activity; therefore, the variation in number and size of GWB may correlate with the activities of miRNA during different stages of the cell cycle and proliferation (Yang et al, 2004;Hatfield et al, 2005;He et al, 2005;O'Donnell et al, 2005;Lian et al, 2006). Interestingly, a recent publication reported that Drosophila siRNA:mRNA or miRNA:mRNA also nucleated the formation of GWB (Eulalio et al, 2007b), an observation that strongly supports our finding that siRNA/miRNA-mediated function is a key regulatory mechanism of GWB assembly. Nonetheless, their data also implicated differences in the regulation of GWB formation in Drosophila from that in human.…”
Section: Regulation Of Gwb Assemblymentioning
confidence: 93%
“…However, recent studies indicate that mRNA decay, NMD and RNAi-mediated gene silencing are functional in Drosophila and mammalian cells lacking detectable microscopic P bodies, suggesting that the formation of P bodies is a consequence of these processes (Chu and Rana, 2006;Eulalio et al, 2007). Here we revealed that a large number of genes whose inactivations enhance the formation of P bodies are also involved in regulating NMD, RNAi-and miRNA-mediated gene silencing, providing a link between the formation of P bodies and these RNA metabolism processes.…”
Section: Role Of Translation In Regulating Rnaimentioning
confidence: 99%
“…Indeed, depletion of P-body components such as LSm1 and RCK/p54 (Chu and Rana, 2006) in human cells has no effect on siRNA silencing, leading to a view that P-bodies are dispensable for siRNA-mediated RNAi. However, depletion of the P-body structural component GW182 has shown mixed results; three reports show that silencing GW182 does inhibit siRNA silencing to a certain extent (Jakymiw et al, 2005;Liu et al, 2005a;Lian et al, 2007), whereas others show no requirement of GW182 for siRNA function (Rehwinkel et al, 2005;Chu and Rana, 2006;Eulalio et al, 2007b). However, siRNAs have been found to localize to P-bodies (Jakymiw et al, 2005), and the number and size of P-bodies were found to increase upon siRNA transfection, in a target-dependant manner (Lian et al, 2007 Lsm1 or RCK/p54, functional siRNAs are capable of inducing P-body reassembly (Lian et al, 2007).…”
mentioning
confidence: 99%